Inferring the diagnostic potential of 18F-FDG-PET/CT in post-renal transplantation from a unique case harboring multiple rare complications - Huang, Zizhen; Zou, Shiwei; Liu, Qian; Qi, Wanling; Sharma, Amit; Wang, Yulu; Jin, Aifang; Schmidt-Wolf, Ingo G. H.; Lu, Ping; Ai, Wuping; Liao, Fengxiang (Frontiers in Medicine, 2024)
Renal transplantation is undoubtedly an effective treatment for patients with end-stage renal disease, but it is certainly not a cure. Patients require lifelong immunosuppression to maintain optimal allograft function, and post-operative risk complications such as cancer in the transplant recipient cannot be ignored. Besides, infection is a silent complication that follows transplantation. Relatedly, herein, we present a report of a 40-year-old patient who underwent renal transplantation and promptly developed a diffuse large B-cell tumor in the liver and Aspergillus infection in the trachea. In addition, an inflammatory necrotizing granuloma was also observed in the muscles. Of importance, we also described the potential of 18F-FDG-PET/CT, which was instrumental in monitoring and evaluating these relevant post-operative complications in this rare case.